Retenční vlastnosti šikmé zelené střechy - Pavela, Martin (Vysoké učení technické v Brně. Fakulta stavební, 2017)
Diplomová práce je zaměřena na analýzu vlivu skladby a sklonu šikmé vegetační střechy na retenční vlastnosti. V praktické části je provedena série měření retenčních vlastností na čtyřech zkušebních modelech. Testování probíhá na skladbách vegetačních střech v inicializačním růstovém období a jedné skladbě se starou střešní pálenou taškou. V teoretické části práce jsou podrobně popsány typy vegetačních střech, historie jejich vývoje v České Republice i v zahraničí a jejich přínosnost.

This diploma thesis is focused on the analysis of the retention effect on the pitch green roof from the selection of different roof sets. Measurements of retention proparties were performed on four semi-scale testing elements. Monitored period was evaluated during initial growing cycle on extensive, biodiverse and icelandic green roof in comparison with roofing tile surface. The theoretical part describes effective water retention management, historical and present development in the Czech Republic and closed European countries of green roofs.
Effect of sloped green roof on to rainwater retention
Keywords: retence šikmé vegetační střechy; retention effect pitch green roof